Evaluation of action recognition algorithms for fall detection applications - Pei, Yubo (Nanyang Technological University, 2024)
As society ages, ensuring the elderly's safety at home, especially fall prevention, has become crucial due to the serious health risks falls pose. Consequently, developing effective fall detection and prevention technologies is a key focus in smart elder care. This dissertation explores a video surveillance-based fall detection method aiming to enhance the elderly's safety and well-being through technological innovations.